2005
DOI: 10.1016/j.vaccine.2005.01.089
|View full text |Cite
|
Sign up to set email alerts
|

Yellow fever vaccine: An updated assessment of advanced age as a risk factor for serious adverse events

Abstract: Chen, Robert T.; and Cetron, Martin S., "Yellow fever vaccine: An updated assessment of advanced age as a risk factor for serious adverse events" (2005 AbstractSince 1996, the scientific community has become aware of 14 reports of yellow fever vaccine (YEL)-associated viscerotropic disease (YEL-AVD) cases and four reports of YEL-associated neurotropic disease (YEL-AND) worldwide, changing our understanding of the risks of the vaccine. Based on 722 adverse event reports after YEL submitted to the U.S. Vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
137
0
13

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(161 citation statements)
references
References 16 publications
11
137
0
13
Order By: Relevance
“…9,10 Advanced age, thymus disease, and other immunosuppressive conditions are major risk factors associated with YF-AVD. 3,[11][12][13] One explanation for the increased reports of vaccineassociated adverse events is increased surveillance and reporting. Interestingly, before the approval of hepatitis A vaccine in 1996, the YF vaccine was commonly given simultaneously with Ig (for hepatitis A prophylaxis) during pretravel immunizations.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Advanced age, thymus disease, and other immunosuppressive conditions are major risk factors associated with YF-AVD. 3,[11][12][13] One explanation for the increased reports of vaccineassociated adverse events is increased surveillance and reporting. Interestingly, before the approval of hepatitis A vaccine in 1996, the YF vaccine was commonly given simultaneously with Ig (for hepatitis A prophylaxis) during pretravel immunizations.…”
Section: Introductionmentioning
confidence: 99%
“…Only patients with serious neurologic adverse events were included, i.e., adverse events that resulted in life-threatening illness, inpatient hospitalization, persistent or significant disability, or death. 15 Data were extracted from medical charts, including demographic variables, past medical story, indication for YF vaccination, concomitant vaccinations, interval between YF vaccination and first symptoms, diagnostic workup, and outcome.…”
mentioning
confidence: 99%
“…11 Likewise, naturally acquired YF is also more likely to be severe among males. 17 Although YF-AND has been the most common serious adverse event associated with YF vaccination, its incidence has been constantly estimated as low, between 0.4 and 0.8 cases per 100,000 doses in the United States, 4,11,15 and in Europe. 16 Of the 23 encephalitis cases reported during 1945-2002 worldwide among > 200 million doses, 16 cases (69.6%) have been reported in newborns and infants < 9 months of age, 18 which suggests that the incidence of post-vaccinal encephalitis is much lower when contraindications for YF vaccine administration are followed, i.e., absolute contraindication for newborns and infants < 6 months of age, and limited use between 6 and 9 months of age (only if risk of disease is significant and other methods of prevention cannot be used).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 All AEFI are monitored by a passive surveillance system known as the Vaccine Adverse Event Reporting System, operated by CDC and the US Food and Drug Administration (FDA). 13 AEFI, following yellow fever vaccination, are typically mild and nonspecific. 14 Interestingly, studies have suggested that there is a higher incidence of local inflammatory events in female vaccine recipients, than in males.…”
mentioning
confidence: 99%